The relationship between the network of non-coding RNAs-molecular targets and N6-methyladenosine modification in tumors of urinary system - Ruiming Li; Chunming Zhu; Yuan Wang; Xia Wang; Yibing Wang; Jiahe Wang; Kefeng Wang (Cell Death and Disease, 2024)
Abstract N6-methyladenosine (m6A) methylation, a prevalent eukaryotic post-transcriptional modification, is involved in multiple biological functions, including mediating variable splicing, RNA maturation, transcription, and nuclear export, and also is vital for regulating RNA translation, stability, and cytoplasmic degradation. For example, m6A methylation can regulate pre-miRNA expression by affecting both splicing and maturation. Non-coding RNA (ncRNA), which includes microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), does not encode proteins but has powerful impacts on transcription and translation. Conversely, ncRNAs may impact m6A methylation by affecting the expression of m6A regulators, including miRNAs targeting mRNA of m6A regulators, or lncRNAs, and circRNAs, acting as scaffolds to regulate transcription of m6A regulatory factors. Dysregulation of m6A methylation is common in urinary tumors, and the regulatory role of ncRNAs is also important for these malignancies. This article provides a systematic review of the role and mechanisms of action of m6A methylation and ncRNAs in urinary tumors.